PENGARUH LATIHAN POWER TUNGKAI MELALUI METODE LONCAT GAWANG TERHADAP TINGGI LONCATAN SPIKE BOLA - Anres Hidayat (Journal of Physical Education and Sport Science, 2021)
The purpose of this study was "to determine the effect of leg power training through the goal jump method on volleyball spike jump height". The method used in this research is the quantitative method. This study uses an experimental design, namely One Group Pretest-Posttest Design. The population in this study was male volleyball extracurricular students at SMP Negeri 2 Cimahi, the sample technique applied in this study was purposive sampling, with 17 students. The instrument was used in vertical jump test research. The results of the pre-test data analysis obtained an average value of 38.0 and the post-test average value of 49.0. There is an effect on increasing the height of the volleyball spike jumps of students at SMP Negeri 2 Cimahi. Therefore, to test the hypothesis using the paired samples t-test, the pre-test and post-test values showed a sig. (2-tailed) value of 0.000 <0.05, so there was a significant difference.